Cognitive Disorders in Children with Cerebral Palsy - Karimova Dilobar (Genius Journals, 2023)
Diagnosis of cognitive disorders in children with cerebral palsy is a difficult task due to the diverse combination with motor, speech and sensory pathology, and therefore requires a differentiated approach. The authors have developed differential diagnostic criteria for distinguishing between mental retardation and mental retardation in children with cerebral palsy. The proposed comprehensive system for the rehabilitation of cognitive disorders includes medical-social and psychological-pedagogical correction and is aimed at compensating for cognitive deficits, developing mental functions, and restoring the mechanisms of social integration in children with cerebral palsy.
Keywords: Cerebral palsy; cognitive impairment; mental retardation